A functional nexus between photoperiod acclimation, torpor expression and somatic fatty acid composition in a heterothermic mammal. - Fritz Geiser; Martin Klingenspor; Bronwyn M McAllan (PLoS ONE, 2013)
The seasonal changes in thermal physiology and torpor expression of many heterothermic mammals are controlled by photoperiod. As function at low body temperatures during torpor requires changes of tissue lipid composition, we tested for the first time whether and how fatty acids are affected by photoperiod acclimation in hamsters, Phodopus sungorus, a strongly photoperiodic species. We also examined changes in fatty acid composition in relation to those in morphology and thermal biology. Hamsters in short photoperiod had smaller reproductive organs and most had a reduced body mass in comparison to those in long photoperiod. Pelage colour of hamsters under short photoperiod was almost white while that of long photoperiod hamsters was grey-brown and black. Short photoperiod acclimation resulted in regular (28% of days) torpor use, whereas all hamsters in long photoperiod remained normothermic. The composition of total fatty acids differed between acclimation groups for brown adipose tissue (5 of 8 fatty acids), heart muscle (4 of 7 fatty acids) and leg muscle (3 of 11 fatty acids). Importantly, 54% of all fatty acids detected were correlated (r(2) = 0.60 to 0.87) with the minimum surface temperature of individuals, but the responses of tissues differed. While some of the compositional changes of fatty acids were consistent with a 'homeoviscous' response, this was not the case for all, including the sums of saturated and unsaturated fatty acids, which did not differ between acclimation groups. Our data identify a possible nexus between photoperiod acclimation, morphology, reproductive biology, thermal biology and fatty acid composition. They suggest that some of the changes in thermal physiology are linked to the composition of tissue and organ fatty acids.